Upaya Peningkatan Kualitas Hasil Belajar Mata Pelajaran Ilmu Pengetahuan Alam Siswa Kelas VIII MTsN 1 Tuban Melalui Kegiatan Laboratorium - Siti Sofiyah (Inovasi-Jurnal Diklat Keagamaan, 2021)
The role of the teacher is very decisive in the implementation of the teaching and learning process activities. Teachers are responsible for developing students' intellectualism so that efforts are needed to apply skill building to acquire knowledge. For this reason, researchers conducted Classroom Action Research (CAR) entitled "Efforts to Improve the Quality of Learning Outcomes in Science Subjects for Class VIII Students of MTsN 1 Tuban through Laboratory Activities". The initial state before the action, students in the research school were generally less enthusiastic about the Teaching and Learning Process activities, for example when the discussion was not able to express their opinions, had difficulty answering LKS questions, tended to be bored, talked with other students, were less able to actively conclude the material that was have been taught, or have not been skilled in using laboratory tools so that the concept is lacking. This Classroom Action Research was carried out in 3 cycles, each cycle beginning with Preliminary Activities, Core Activities and Closing Activities. Data collection was carried out using 4 instruments including observation instruments for teachers, observations of students during learning, interview guidelines for students, and assessment sheets for the process and assessment of daily tests. The data obtained were analyzed quantitatively and qualitatively. The subjects taken were class VIII A and VIII B. The study was conducted from July to October 2019. After conducting classroom action research through lectures, discussions and experiments based on the optimization of laboratory use, the results obtained were students who were brave and able to express opinions, were active in discussion activities, were able to conclude and summarize the material taught by the teacher, skilled in using laboratory tools, interested and happy to learn Biology as evidenced by the daily test scores before the CAR and after the CAR tended to increase.